2021
DOI: 10.3390/atmos12111492
|View full text |Cite
|
Sign up to set email alerts
|

The Connection between Extreme Precipitation Variability over Monsoon Asia and Large-Scale Circulation Patterns

Abstract: Spatial and temporal variability in precipitation has been dramatically changed due to climate variability and climate change over the global domain. Increasing in extreme precipitation events are pronounced in various regions, including monsoon Asia (MA) in recent decades. The present study evaluated precipitation variability in light of intensity, duration, and frequency with several extreme precipitation climate change indices developed by the Expert Team on Climate Change Detection Indices (ETCCDI) over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Extreme precipitation has also shown an increasing trend with significant spatial heterogeneity [15,[29][30][31]. Many scholars attribute this climate change to the internal variability of the climate system, such as the Southern Oscillation, the North Atlantic Oscillation and the Asian subtropical jet [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Extreme precipitation has also shown an increasing trend with significant spatial heterogeneity [15,[29][30][31]. Many scholars attribute this climate change to the internal variability of the climate system, such as the Southern Oscillation, the North Atlantic Oscillation and the Asian subtropical jet [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…However, Du et al (2022) documented that extreme precipitation over consecutive days may increase due to warmer climates. Sunilkumar et al (2021) reported that extreme rainfall events have increased in various regions, including monsoon Asia, in recent decades. During the OND season, tropical cyclones over the BoB play a very crucial role in the daily rainfall activities over the PI.…”
Section: Environmental Conditions For Cyclogenesis Over the Bay Of Be...mentioning
confidence: 99%
“…The position of WPSH is not prone to jump north but to maintain a southerly position, which is conducive to transporting the water vapor from the Pacific Ocean and the South China Sea to the MLYR continuously. The cold air from the high latitudes southwards converges with the warm and humid air in the MLYR, which is conducive to the formation of continuous heavy rainstorms (Khadgarai et al, 2021;Xia et al, 2022). produce large scale precipitation during its activity [54,55].…”
Section: Response Of Extreme Precipitation Indices To Atmospheric Cir...mentioning
confidence: 99%